Multicatalytic Enantioselective Borrowing Hydrogen δ-Lactonization Strategy from β-Keto Esters and Allylic Alcohols - Quintard, Adrien; Roudier, Mylène; Rodriguez, Jean (Synthesis, 2018)
By combining an iron-catalyzed borrowing hydrogen of allylic alcohols with an enantioselective organocatalyzed Michael addition of β-keto esters followed by a subsequent DBU-promoted lactonization different enantioenriched δ-lactones have been synthesized with good enantioselectivities. The valuable building blocks, featuring in some cases challenging quaternary stereocenters, have been obtained with >90% ee.
Keywords: organocatalysis; iron catalysis; lactone synthesis; borrowing hydrogen; multi-catalysis